Potensi Pengembangan Wisata Di Kawasan Tahura Ngurah Rai Bali Berdasarkan Kajian Hukum Kehutanan Ri - I Nyoman Winia; I Made Adi Widnyana (Sekolah Tinggi Agama Hindu Mpu Kuturan Singaraja, 2021)
Bali is famous as a world tourist destination, various developments are carried out by the Government to be able to optimize the tourism sector, so as to provide maximum regional revenue. With the rules of regional autonomy, each region is racing to innovate and creativity in developing the tourism potential of the region, so that many potentials that were initially considered unhelpful, began to be looked at and developed. Including the area of Forest Park Raya (Tahura), which was originally considered by the community as a protected area that serves to support, protect and as an ecosystem from the existence of habitats that live in it. Along with the development of the utilization of Tahura through tourism development can be done, but still with due regard to the provisions of the applicable law, so that not all areas of forest park can be developed for tourism potential. Similarly, in the area of Forest Park Raya (TAHURA) Ngurah Rai Bali which has Tahura area in the form of mangrove forests. Therefore, the desire of the local community to develop the Tahura Ngurah Rai area must still pay attention to the provisions of the law, so that the development of tourism is not illegal. Based on this problem formulated in this paper is about how to arrange tourism development in the Forest Park Area and How the status of the Tahura Ngurah Rai area and the potential for tourism development in the area. So the expected purpose is to be able to provide legality guarantees in the development of tourism conducted in the Tahura Ngurai Rai area based on the prevailing legal provisions From the analysis conducted resulted in that the arrangement of tourism development in the Tahura area, can be done using the legal basis of Natural Tourism Management that can only be done in areas that have the status of utilization blocks. While the status of the area Tahura ngurah rai not all are in the position of the utilization block, so not all areas Tahura ngurah rai can be developed for the development of tourism potential.